Enhancing Biology Students Motivation Through Classroom Action Research Based STAD Learning Model - Erna Mufidatul Hijriyah; Ericka Darmawan; Muhammad Rizal Akbar Zamzami (Indonesian Journal of Biology Education, 2018)
This study was conducted to determine the effectiveness of Student Teams Achievement Divisions (STAD) learning models in Biology subjects in improving student learning motivation. This research is a classroom action research conducted in 2 cycles, each cycle consists of four stages consisting of action planning, action implementation, observation, and reflection. The research subjects were students of class XI IPA 2 Malang State Senior High School 6, totaling 37 people consisting of 10 male students and 27 female students. The study was carried out for 4 months, in the nervous system material (structure, function, impulse delivery principle, reflex motion, nervous system composition, nervous system in animals and the influence of drugs on the nervous system) as well as material about the hormone system (hormonal characteristics, neural and hormonal relationships, endocrine glands, vertebrate hormones, and invertebrate hormones). Learning motivation data is obtained by comparing the motivation score of cycle I and cycle II, the student learning motivation test consists of 30 questions with five answer choices, namely the scores of one, two, three, four, and five. Determination of the success of student motivation actions is determined by scoring the assessment of Benchmark Reference (PAP) of the State University of Malang (UM) using a Likert scale. The conclusion in this study is that the STAD model can improve student learning motivation, as it is proved by the increase in the percentage from 61.5% (moderate) in the first cycle to 83.9% (good) in the second cycle